The Malay cultural landscape characteristics for the Islamic aristocrat town in Kelantan, Malaysia - Nik Mohammad, Nik Mastura; Ismail, Nor Atiah; Utaberta, Nangkula (Universitas Islam Negeri (UIN) Maulana Malik Ibrahim Malang, 2021)
The Malay cultural landscape has become an integral part of examining the cultural significance in Malaysia. Thus, the main objective of the study is to determine the impact of the visual characteristics of the built cultural landscape in conserving and preserving Kota Bharu as an aristocratic area in this modern era. Kota Bharu is one of the Islamic cities in Malaysia. This study embarks into a quantitative study using a mixed-method. A significant implication is to propose a significant model to value the Malay cultural heritage and preserve the culture and spirit among the Kelantanese Malay population who live in the modern era.